Law and justice in Jerusalem, Babylon and Hellas - Daphnē, Euangelia; Elsas, Christoph (Studien zur Theologie der Septuaginta, 2021)
The present volume rounds off the trilogy of conference contributions on the theology of the Septuagint. As with the two preceding volumes (WUNT 387 and 432), experts who have earned particular merit in their individual fields of research and whose methodical reflection is rooted in a love of the Greek translation of the Old Testament are given free rein to express themselves on the »past - present - future« triptych of the Septuagint.